Aluminum-based composite material, preparation method thereof and electronic device
By forming a metal protective layer on the surface of the aluminum-based substrate and electroplating nickel and gold plating layer by layer, the problem of insufficient corrosion resistance of the existing aluminum-based substrate coating is solved, and higher corrosion resistance and oxidation resistance are achieved. Simplified process flow.
Patent Information
- Application Number
- CN202311021148.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2025-02-18
AI Technical Summary
The chemical nickel-gold plating of existing aluminum-based materials is prone to corrosion, resulting in insufficient corrosion resistance and oxidation resistance, and poor flatness and denseness of the coating.
By forming a metal protective layer on the surface of the aluminum-based substrate and forming a nickel plating layer by layer using an electroplating process, the uniformity and density of the plating layer are ensured.
The corrosion resistance and oxidation resistance of the coating are improved, the mutual diffusion of nickel and gold elements is avoided, the problem of black pads is eliminated, and the process is short and the cost is low.
Smart Images

Figure CN119465329A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of electrical materials, and in particular to aluminum-based composite materials, preparation methods thereof, and electronic devices. Background Art
[0002] Aluminum-based materials have the advantages of high thermal conductivity, adjustable thermal expansion coefficient, low density, strong dimensional stability, and excellent electrical properties, making them widely used in the preparation of printed circuit boards, circuit packaging structures, etc. In order to achieve the weldability of aluminum-based materials and improve their physical and chemical properties (such as reducing porosity and improving corrosion resistance), electroless nickel immersion gold (ENIG) is currently commonly used to form nickel and gold plating layers on the surface of aluminum-based materials.
[0003] Chemical nickel-gold currently has the following problems: the nickel chemical plating layer easily dissolves and corrodes the gold chemical plating layer, which not only produces the "black pad syndrome", but also reduces the surface wettability of the gold chemical plating layer, making it impossible to prepare electrical interconnection structures through the bonding process. In the related technology, either by doping P, Cu and other impurities in the nickel chemical plating layer, or by setting an inert Pd layer between the nickel chemical plating layer and the gold chemical plating layer, the corrosion resistance of the nickel plating layer is improved.
[0004] However, the chemical plating layer prepared by the related technology has poor flatness and density, which makes the corrosion resistance and oxidation resistance of the coating not stable for a long time.
[0005] Public Content
[0006] In view of this, the present disclosure provides an aluminum-based composite material and a preparation method thereof, and an electronic device, which can solve the technical problems in the related art.
[0007] In one aspect, a method for preparing an aluminum-based composite material is provided, the method for preparing the aluminum-based composite material comprising:
[0008] Purifying the aluminum-based substrate to obtain a purified aluminum-based substrate;
[0009] forming a metal protective layer on the surface of the purified aluminum-based substrate to obtain a first composite material intermediate;
[0010] Performing a first electroplating treatment on the first composite intermediate so that the metal protective layer is corroded to form a first metal plating layer on the surface of the aluminum-based substrate to obtain a second composite intermediate;
[0011] The second composite material intermediate is subjected to a second electroplating treatment, so that a second metal coating is formed on the surface of the first metal coating, thereby obtaining the aluminum-based composite material.
[0012] The method for preparing an aluminum-based composite material provided by the embodiment of the present disclosure forms a metal protective layer on the surface of an aluminum-based substrate. The metal protective layer can protect the aluminum-based substrate from forming an oxide film on its surface. When performing a first electroplating treatment, the metal protective layer can be corroded as a sacrificial layer, and the first metal coating replaces the metal protective layer and adheres to the surface of the aluminum-based substrate, which not only helps to improve the bonding strength between the first metal coating and the aluminum-based substrate, but also can prevent the aluminum-based substrate from being oxidized and corroded by the plating solution during the electroplating process. Because the aluminum-based substrate is relatively active, it is very easy to be corroded in the plating solution, and the provision of the metal protective layer effectively solves this problem. Furthermore, the second composite material intermediate having the first metal coating is subjected to a second electroplating treatment, so that a second metal coating is formed on the surface of the first metal coating to obtain an aluminum-based composite material. In the aluminum-based composite material, the aluminum-based substrate, the first metal coating, and the second metal coating are sequentially stacked, and the first metal coating and the second metal coating are formed by electroplating process, which not only makes the first metal coating and the second metal coating uniform and dense, so as to avoid element diffusion between the two, which is beneficial to improve the stability of the coating, but also makes the surface of the first metal coating and the second metal coating smooth. In summary, the preparation method of the aluminum-based composite material provided by the embodiment of the present disclosure can not only improve the compactness and smoothness of the coating, thereby improving the corrosion resistance and oxidation resistance of the coating, but also does not need to introduce other inert precious metals in the preparation process, and also has the advantages of short operation process, convenience, high efficiency, strong reliability, low cost, etc.
[0013] In some possible implementations, the metal protective layer includes a zinc layer. The zinc layer can not only effectively protect the aluminum-based substrate, but also has a relatively simple and reliable preparation process and will not damage the aluminum-based substrate.
[0014] In some possible implementations, forming a metal protective layer on the surface of the purified aluminum-based substrate to obtain a first composite material intermediate includes:
[0015] Placing the purified aluminum-based substrate in a zinc plating solution for zinc plating, forming a zinc layer on the surface of the purified aluminum-based substrate, and obtaining a first composite material intermediate;
[0016] The zinc plating solution comprises the following components:
[0017] 50g / L-200g / L of sodium hydroxide, 5g / L-50g / L of potassium sodium tartrate, 1g / L-10g / L of zinc oxide, 0.2g / L-2g / L of iron and ferrous compounds, and water as the balance so that the pH value of the zinc plating solution is 12-14.
[0018] The zinc layer is plated on the surface of the aluminum-based substrate by chemical plating, which is easy to operate and makes the thickness of the zinc layer controllable. By using the above-mentioned zinc plating solution to treat the aluminum-based substrate, the Al2O3 film can be removed and contained, thereby exposing the aluminum-based surface of the aluminum-based substrate to present an ideal surface state before plating, so that after the zinc layer is sacrificed, the surface of the aluminum-based substrate can grow a first metal plating layer.
[0019] In some possible implementations, the thickness of the metal protection layer is 1 nm-100 nm.
[0020] In some possible implementations, the first metal coating includes a nickel coating or a nickel-phosphorus alloy coating;
[0021] The second metal plating layer includes a gold plating layer.
[0022] In this way, an aluminum-based composite material with a nickel-plated layer and a gold-plated layer can be prepared. The nickel-plated layer and the gold-plated layer are formed by an electroplating process, so that the two are uniform, dense and flat. The dense nickel-plated layer and the gold-plated layer avoid mutual diffusion of nickel elements and gold elements, and both are pure phases without doping with other miscellaneous elements, thereby avoiding the Giovanni effect and eliminating the black pad problem. This not only improves the stability of the nickel-plated layer and the gold-plated layer, making their corrosion resistance and oxidation resistance more stable, but also the surface flatness and uniform texture of the coating are conducive to welding and gold wire bonding.
[0023] In some possible implementations, the first metal plating layer is a nickel plating layer, and the first electroplating treatment uses a nickel plating solution, which includes the following components: 1g / L-50g / L nickel sulfate, 1g / L-50g / L nickel chloride, 1g / L-50g / L nickel methanesulfonate, 1g / L-50g / L hydrochloric acid, 1g / L-10g / L main brightener, 0.1g / L-1g / L auxiliary brightener, and the balance is water. The nickel plating solution using the above formula has the advantages of stable chemical properties and long service life.
[0024] In some possible implementations, during the first electroplating process, the current density is 0.1ASD-5ASD, and the electroplating temperature is 45° C.-65° C. By defining the operating parameters of nickel electroplating as above, it has the advantages of increasing the plating rate and making the coating thickness uniform.
[0025] In some possible implementations, the second metal plating layer is a gold plating layer, and the second electroplating treatment uses a gold plating solution, which includes the following components in the following proportions: 10g / L-20g / L gold trichloride, 50g / L-130g / L sodium sulfite, 30g / L-50g / L ethylenediaminetetraacetic acid, 30g / L-50g / L citric acid, 50g / L-80g / L potassium chloride, and the balance is water. The gold plating solution using the above formula has the advantages of increasing the plating rate and making the coating thickness uniform.
[0026] In some possible implementations, during the second electroplating process, the current density is 0.1ASD-5ASD, and the electroplating temperature is 30° C.-45° C. By defining the operating parameters of electroplating gold as above, it has the advantages of increasing the plating rate and making the plated film thickness uniform.
[0027] In some possible implementations, the method for preparing the aluminum-based composite material further includes: before the purified aluminum-based substrate is subjected to galvanizing, the purified aluminum-based substrate is subjected to surface etching treatment, so that a rough structure is formed on the surface of the purified aluminum-based substrate;
[0028] The rough structure is used to enhance the bonding force between the aluminum-based substrate and the first metal coating layer.
[0029] In some possible implementations, the surface etching treatment is performed by placing the cleaned aluminum-based substrate in an etching solution;
[0030] The etching solution comprises the following components:
[0031] 10g / L-50g / L tetramethylammonium hydroxide, 10g / L-50g / L disodium ethylenediaminetetraacetate, 5g / L-20g / L zinc oxide, 5g / L-20g / L barbituric acid, 0.1g / L-1g / L soluble silver salt, and water as the balance so that the pH value of the etching solution is 10-13.
[0032] In another aspect, an aluminum-based composite material is provided, the aluminum-based composite material comprising an aluminum-based substrate, a first metal coating, and a second metal coating arranged in sequence;
[0033] The unit cell diameter of the first metal coating is less than or equal to 100 nm;
[0034] The unit cell diameter of the second metal coating layer is less than or equal to 100 nm.
[0035] In some possible implementations, a surface of the aluminum-based substrate that is combined with the first metal coating layer has a rough structure, and the rough structure is used to enhance the bonding force between the aluminum-based substrate and the first metal coating layer.
[0036] On the other hand, an electronic device is provided, comprising a device body and a pad structure connected to the device body, wherein the pad structure is prepared using any of the above-mentioned aluminum-based composite materials.
[0037] The aluminum-based composite material provided by the embodiment of the present disclosure has a unit cell diameter of a nickel coating less than or equal to 100 nm, and a dense lattice in the nickel coating, so that the nickel coating is uniform and dense. The unit cell diameter of a gold coating is less than or equal to 100 nm, and a dense lattice in the gold coating, so that the gold coating is uniform and dense, and has an excellent covering effect on the nickel coating. The dense nickel coating and gold coating avoid mutual diffusion of nickel and gold elements, thereby avoiding the Giovanni effect and the black pad problem, which not only improves the stability of the nickel coating and the gold coating, making their corrosion resistance and oxidation resistance more stable, but also the gold coating with a flat surface and uniform texture is also conducive to welding and gold wire bonding.
[0038] In some possible implementations, the electronic device includes: a chip and a printed circuit board. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A flow chart of preparing an exemplary aluminum-based composite material provided in an embodiment of the present disclosure;
[0040] Figure 2 Another exemplary preparation process of aluminum-based composite materials provided in the present disclosure;
[0041] Figure 3 The SEM images of the nickel-plated layer of the aluminum-based composite material provided in Example 1 at different magnifications;
[0042] Figure 4 SEM images of the nickel-plated layer of the aluminum-based composite material provided in Comparative Example 1 at different magnifications;
[0043] Figure 5 The SEM images of the gold-plated layer of the aluminum-based composite material provided in Example 1 at different magnifications;
[0044] Figure 6 SEM images of the gold-plated layer of the aluminum-based composite material provided in Comparative Example 1 at different magnifications. DETAILED DESCRIPTION
[0045] The technical solutions in the embodiments of the present disclosure will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0046] At present, chemical nickel-gold is also called chemical nickel-gold plating. Nickel plating and gold plating are formed on the surface of aluminum-based materials in sequence by chemical plating. However, the grains of nickel plating and gold plating formed by chemical plating are relatively loose, which makes it easy for nickel and gold elements to diffuse with each other, and then the two react electrochemically to produce "black pad syndrome". It can be seen that the stability of nickel plating and gold plating is poor, and this also makes the plating surface uneven and uneven, and the surface wettability of gold plating is reduced. Not only can solder paste and the like not be naturally spread on it, which is not conducive to welding, but also the gold wire cannot form electrical interconnection with the surface of gold plating through the bonding process.
[0047] In view of the technical problems existing in the related art, the present disclosure provides a method for preparing an aluminum-based composite material, as shown in the attached Figure 1 As shown, the preparation method of the aluminum-based composite material includes:
[0048] Step S11, purifying the aluminum-based substrate to obtain a purified aluminum-based substrate.
[0049] Step S12: forming a metal protective layer on the surface of the purified aluminum-based substrate to obtain a first composite material intermediate.
[0050] Step S13: performing a first electroplating treatment on the first composite material intermediate so that the metal protective layer is corroded to form a first metal plating layer on the surface of the aluminum-based substrate to obtain a second composite material intermediate.
[0051] Step S14: performing a second electroplating treatment on the second composite material intermediate so that a second metal coating is formed on the surface of the first metal coating to obtain an aluminum-based composite material.
[0052] The method for preparing an aluminum-based composite material provided by the embodiment of the present disclosure forms a metal protective layer on the surface of an aluminum-based substrate. The metal protective layer can protect the aluminum-based substrate from forming an oxide film on its surface. When performing a first electroplating treatment, the metal protective layer can be corroded as a sacrificial layer, and the first metal coating replaces the metal protective layer and adheres to the surface of the aluminum-based substrate, which not only helps to improve the bonding strength between the first metal coating and the aluminum-based substrate, but also can prevent the aluminum-based substrate from being oxidized and corroded by the plating solution during the electroplating process. Because the aluminum-based substrate is relatively active, it is very easy to be corroded in the plating solution, and the provision of the metal protective layer effectively solves this problem. Furthermore, the second composite material intermediate having the first metal coating is subjected to a second electroplating treatment, so that a second metal coating is formed on the surface of the first metal coating to obtain an aluminum-based composite material. In the aluminum-based composite material, the aluminum-based substrate, the first metal coating, and the second metal coating are stacked in sequence, and the first metal coating and the second metal coating are formed by using an electroplating process, which not only makes the first metal coating and the second metal coating uniform and dense to avoid element diffusion between the two and is beneficial to improving the stability of the coating, but also makes the surfaces of the first metal coating and the second metal coating smooth.
[0053] In summary, the preparation method of the aluminum-based composite material provided in the embodiment of the present disclosure can not only improve the density and smoothness of the coating, thereby improving the corrosion resistance and oxidation resistance of the coating, but also does not require the introduction of other inert precious metals during the preparation process, and also has the advantages of short, convenient, efficient, reliable and low-cost operation process.
[0054] In some examples, the first metal plating layer includes a nickel plating layer or a nickel-phosphorus alloy plating layer; the second metal plating layer includes a gold plating layer. For example, the first metal layer is a nickel plating layer, and the second metal plating layer is a gold plating layer, so as to realize the combination of the aluminum-based substrate with nickel and gold, and obtain an electroplated Ni-Au structure. In this way, the formed aluminum-based composite material includes an aluminum-based substrate, a nickel plating layer, and a gold plating layer stacked in sequence, so that it can be used for a pad structure.
[0055] It can be seen that in the preparation method of the aluminum-based composite material provided by the embodiment of the present disclosure, when the first electroplating treatment is performed, the metal protective layer can be corroded as a sacrificial layer, and the dense and flat nickel-plated layer replaces the metal protective layer and adheres to the surface of the aluminum-based substrate. Electroplating gold is performed on the second composite intermediate having a nickel-plated layer, so that the surface of the dense and flat nickel-plated layer continues to form a dense and flat gold-plated layer, and an aluminum-based composite material is obtained. In the aluminum-based composite material, the nickel-plated layer and the gold-plated layer are formed by electroplating technology, so that the two are uniform, dense and flat, and the dense nickel-plated layer and the gold-plated layer avoid the mutual diffusion of nickel and gold elements, and both are pure phases without other impurity elements. Doping, thereby avoiding the Giovanni effect and eliminating the black pad problem, not only improves the stability of the nickel-plated layer and the gold-plated layer, making its corrosion resistance and oxidation resistance more stable, but also the surface flatness and uniform texture of the coating are also conducive to welding and gold wire bonding.
[0056] The following is a more detailed description of each step and its function in the aluminum-based composite material.
[0057] In step S11, the aluminum-based substrate is purified to obtain a purified aluminum-based substrate to ensure that impurities on the surface of the aluminum-based substrate are removed, wherein the impurities include inorganic impurities and organic impurities, and the organic impurities include oily substances.
[0058] In some examples, the aluminum-based substrate is purified, including: placing the aluminum-based substrate in a decontamination solution, soaking it at 40°C-70°C for 3min-10min, using the decontamination solution to decompose organic impurities such as grease and dirt on the aluminum-based substrate, and the organic impurities are separated from the surface of the aluminum-based substrate and enter the decontamination solution along with inorganic impurities.
[0059] Exemplarily, the immersion temperature during purification treatment includes but is not limited to: 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, etc., and the immersion time includes but is not limited to: 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min, etc.
[0060] In some examples, the impurity removal solution includes components in the following proportions: 3g / L-30g / L of sodium hydroxide, 5g / L-50g / L of carbonate, 5g / L-20g / L of phosphate, 1g / L-20g / L of boron compound, 1g / L-10g / L of surfactant, and water as the balance so that the pH value of the impurity removal solution is 8-10.
[0061] The concentration of sodium hydroxide includes but is not limited to: 5g / L, 10g / L, 15g / L, 20g / L, 25g / L, etc.
[0062] The carbonate can be at least one of sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate. The concentration of the carbonate includes but is not limited to: 5g / L, 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, etc.
[0063] The phosphate can be at least one of sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, potassium phosphate, potassium monohydrogen phosphate, and potassium dihydrogen phosphate. The concentration of the phosphate includes but is not limited to: 5g / L, 10g / L, 12g / L, 15g / L, 18g / L, 20g / L, etc.
[0064] The boron compound can be at least one of dimethylamine borane, trimethylammonium borane, diethylammonium borane, triethylammonium borane, and dicyclohexylammonium borane. The concentration of the boron compound includes but is not limited to: 5g / L, 10g / L, 12g / L, 15g / L, 18g / L, 20g / L, etc.
[0065] The surfactant can be an anionic surfactant or a nonionic surfactant, for example, at least one of alkylphenol polyoxyethylene ether and polyoxyethylene alkyl alcohol amide. The concentration of the surfactant includes but is not limited to: 1g / L, 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, etc.
[0066] In the embodiment of the present disclosure, the material of the aluminum-based substrate can be pure aluminum or an aluminum alloy. Some examples of aluminum alloys include but are not limited to the following: Al-Si alloy (Si content is 0.5wt%-1wt%), Al-Cu alloy (Cu content is 0.5wt%-1wt%), Al-Si-Cu alloy (Si and Cu are in any proportion, but the total content of the two is less than or equal to 1wt%).
[0067] In step S12, a metal protective layer is formed on the surface of the purified aluminum-based substrate to obtain a first composite material intermediate. It can be seen that the first composite material intermediate includes the aluminum-based substrate and the metal protective layer located on the surface of the aluminum-based substrate.
[0068] In some examples, the metal protective layer may cover all surfaces of the aluminum-based substrate to achieve all-round protection of the aluminum-based substrate. Of course, the metal protective layer may also be arranged on only one surface of the aluminum-based substrate.
[0069] Under the premise of not damaging the aluminum-based substrate, the metal protective layer can be formed on the surface of the aluminum-based substrate in a variety of ways, for example, chemical plating and the like can be used.
[0070] In the embodiments of the present disclosure, metals that can serve as sacrificial layers during nickel electroplating without damaging the aluminum-based substrate can be used to prepare metal protective layers. For example, the metal protective layer includes but is not limited to a zinc layer. The zinc layer can not only effectively protect the aluminum-based substrate, but also its preparation process is relatively simple and reliable and will not cause damage to the aluminum-based substrate.
[0071] When the metal protective layer is a zinc layer, the embodiment of the present disclosure forms a metal protective layer on the surface of the purified aluminum-based substrate to obtain a first composite material intermediate, including: placing the purified aluminum-based substrate in a zinc plating solution for zinc plating, forming a zinc layer on the surface of the purified aluminum-based substrate, and obtaining a first composite material intermediate.
[0072] The zinc layer is plated on the surface of the aluminum-based substrate by chemical plating. The operation is simple and the thickness of the zinc layer can be controlled. For example, the thickness of the zinc layer can be adjusted by adjusting at least one of the following parameters: the concentration of zinc oxide in the zinc plating solution and the time of the zinc plating treatment.
[0073] In some examples, the zinc plating solution includes components in the following proportions: 50 g / L-200 g / L of sodium hydroxide, 5 g / L-50 g / L of sodium potassium tartrate, 1 g / L-10 g / L of zinc oxide, 0.2 g / L-2 g / L of iron and ferrous compounds, and water as the balance so that the pH value of the zinc plating solution is 12-14.
[0074] The concentration of sodium hydroxide includes but is not limited to: 50g / L, 60g / L, 70g / L, 80g / L, 90g / L, 100g / L, 110g / L, 120g / L, 130g / L, 140g / L, 150g / L, 160g / L, 170g / L, 180g / L, 190g / L, 200g / L, etc.
[0075] The concentration of potassium sodium tartrate includes but is not limited to: 5g / L, 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, etc.
[0076] The concentration of zinc oxide includes but is not limited to: 1g / L, 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, etc.
[0077] The iron compound may be at least one of ferric chloride, ferric sulfate, ferric nitrate, and ferrocene, and the ferrous compound may be at least one of ferrous sulfate and ferrous gluconate. The concentration of the iron compound or ferrous compound includes, but is not limited to, 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.5 g / L, 0.6 g / L, 0.7 g / L, 0.8 g / L, 0.9 g / L, 1 g / L, 1.1 g / L, 1.2 g / L, 1.3 g / L, 1.4 g / L, 1.5 g / L, 1.6 g / L, 1.7 g / L, 1.8 g / L, 1.9 g / L, 2 g / L, etc.
[0078] The zinc plating solution is an alkaline solution. Zinc oxide ZnO dissolves in the alkaline solution to form Zn(OH)4 2- , so that the aluminum-based substrate undergoes the following replacement reaction in the above-mentioned zinc plating solution:
[0079] Al+Zn(OH)4 2- →AlO 2- +Zn+H2O+OH - +1 / 2H2, it can be seen that during the galvanizing process, the Al2O3 film is removed and contained, and the Zn element is replaced, so that a zinc layer is formed on the surface of the aluminum-based substrate to prevent the regeneration of the Al2O3 film on the aluminum-based substrate.
[0080] By using the above-mentioned zinc plating solution to treat the aluminum-based substrate, the Al2O3 film can be removed and contained, thereby exposing the aluminum-based surface of the aluminum-based substrate and making it present an ideal surface state before plating. In this way, after the zinc layer is sacrificed, the surface of the aluminum-based substrate can grow the first metal plating layer.
[0081] In some examples, the temperature of the galvanizing treatment is 20°C-30°C, and the time of the galvanizing treatment is 5s-20s. By way of example, the temperature of the galvanizing treatment includes but is not limited to 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, etc., and the time of the galvanizing treatment includes but is not limited to 5s, 6s, 7s, 8s, 9s, 10s, 11s, 12s, 13s, 14s, 15s, 16s, 17s, 18s, 19s, 120s, etc.
[0082] By setting the operating parameters of the galvanizing treatment within the above ranges, there are advantages in that the surface of the aluminum-based substrate can be leveled and the formation of an oxide film can be prevented.
[0083] In some examples, the purified aluminum-based substrate is placed in a zinc plating solution for zinc plating, and a zinc layer is formed on the surface of the purified aluminum-based substrate to obtain a first composite material intermediate, including:
[0084] The purified aluminum-based substrate is placed in a zinc plating solution for a first zinc plating treatment, and a zinc layer to be removed is formed on the surface of the purified aluminum-based substrate.
[0085] The aluminum-based substrate with the zinc layer to be removed on the surface is pickled to remove the zinc layer to obtain the aluminum-based substrate with a bare surface.
[0086] The aluminum-based substrate with exposed surface is subjected to a second zinc plating treatment to form a target zinc layer on the exposed surface of the aluminum-based substrate to obtain a first composite material intermediate.
[0087] The first formed zinc layer is stripped and removed by acid, which is conducive to making the exposed surface of the aluminum-based substrate present a better plating state, and the exposed surface of the aluminum-based substrate is further zinc-plated again, so as to obtain a zinc layer with a stronger activation effect, a denser and smoother surface.
[0088] For example, the first galvanizing treatment is performed at a temperature of 20°C-30°C and a time of 8s-20s. The second galvanizing treatment is performed at a temperature of 20°C-30°C and a time of 5s-20s.
[0089] Exemplarily, pickling uses a nitric acid solution with a mass concentration of 20%-40%, for example, a nitric acid solution with a mass concentration of 30% can be used. The pickling temperature can be 20°C-30°C, including but not limited to: 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, etc. The pickling time can be 1s-5s, including but not limited to: 1s, 2s, 3s, 4s, 5s, etc.
[0090] In some examples, the thickness of the metal protective layer, such as the zinc layer, is 1 nm-100 nm, and further, the thickness is 1 nm-50 nm, which includes but is not limited to 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc.
[0091] The metal protective layer may be continuous or discontinuous. For example, when the thickness of the metal protective layer is less than 20 nm, the metal protective layer may be discontinuous and distributed in dispersed islands.
[0092] In step S13, the first composite material intermediate is subjected to a first electroplating treatment, so that the metal protective layer is corroded, thereby forming a first metal plating layer on the surface of the aluminum-based substrate, and obtaining a second composite material intermediate.
[0093] Exemplarily, the first metal coating is a nickel coating, and the first electroplating treatment uses a nickel plating solution. During the nickel electroplating process, the nickel plating solution corrodes the metal protective layer, such as the zinc layer, and the formed nickel coating is formed on the surface of the exposed aluminum-based substrate. Since the nickel coating obtained by electroplating has fine grain growth, a dense and uniform nickel coating is obtained by electroplating on the surface of the aluminum-based substrate, which can effectively resist oxidation and corrosion.
[0094] In some examples, the nickel plating solution provided by the embodiments of the present disclosure includes components in the following proportions: 1g / L-50g / L nickel sulfate, 1g / L-50g / L nickel chloride, 1g / L-50g / L nickel methane sulfonate, 1g / L-50g / L hydrochloric acid, 1g / L-10g / L main brightener, 0.1g / L-1g / L auxiliary brightener, and the balance is water.
[0095] The nickel plating solution of the above formula has the advantages of stable chemical properties, long life, stable and controllable nickel plating process, dense and smooth nickel plating layer, etc. The mass concentration of hydrochloric acid can be 30%-40%, for example, hydrochloric acid with a mass concentration of 36% is used.
[0096] The concentration of nickel sulfate includes but is not limited to: 2g / L, 5g / L, 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, etc.
[0097] The concentration of nickel chloride includes but is not limited to: 1g / L, 5g / L, 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, etc.
[0098] The concentration of nickel methanesulfonate includes but is not limited to: 2g / L, 6g / L, 10g / L, 17g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, etc.
[0099] The concentration of hydrochloric acid includes but is not limited to: 2g / L, 5g / L, 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, etc.
[0100] The concentration of the main brightener includes but is not limited to: 1g / L, 2g / L, 3g / L, 4g / L, 5g / L, 6g / L, 7g / L, 8g / L, 9g / L, 10g / L, etc.
[0101] The main brightener includes, but is not limited to, at least one of sodium o-sulfonylbenzene imide, diphenylsulfinic acid, coumarin (oxanaphthophenone), 1,4-butynediol, pyridine propane sulfonic acid inner salt, N,N-diethylpropargylamine, and ethoxylated propargyl alcohol.
[0102] The concentration of the auxiliary brightener includes but is not limited to: 0.2g / L, 0.3g / L, 0.4g / L, 0.5g / L, 0.6g / L, 0.7g / L, 0.8g / L, 0.9g / L, 1g / L, etc.
[0103] The auxiliary brightener includes, but is not limited to, at least one of sodium vinyl sulfonate, sodium styrene sulfonate, sodium allyl sulfonate, allyl sulfonamide, and sodium propyne sulfonate.
[0104] In some examples, during the first electroplating process, the current density is 0.1ASD-5ASD, and the electroplating temperature is 45° C.-65° C. By defining the electroplating nickel operation parameters as above, it has the advantages of increasing the plating rate, making the coating thickness uniform, and making the film layer dense and flat.
[0105] According to tests, the plating rate of the embodiment of the present disclosure during nickel plating can reach 1.5 μm / min, compared with the plating rate of chemical plating of 0.15 μm / min, which shortens the process time of the embodiment of the present disclosure by 5 to 10 times.
[0106] Exemplarily, the current density includes but is not limited to 0.5ASD, 1ASD, 1.1ASD, 1.2ASD, 1.3ASD, 1.4ASD, 1.5ASD, 1.6ASD, 1.7ASD, 1.8ASD, 1.9ASD, 2ASD, 2.1ASD, 2.2ASD, 2.3ASD, 2.4ASD, 2.5ASD, 2.6ASD, 2.7ASD, 2.8ASD, 2.9ASD, 3ASD, 3.1ASD, 3.2ASD, 3.3ASD, 3.4ASD, 3.5ASD, 4ASD, 4.5ASD, 5ASD, etc.
[0107] Electroplating temperatures include but are not limited to: 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, etc.
[0108] In some examples, the electroplating time during nickel plating may be 1 minute to 5 minutes, and the thickness of the nickel plating layer may be controlled by controlling at least one of the current density and the electroplating time. Exemplarily, the thickness of the nickel plating layer may be 0.5 μm to 5 μm.
[0109] The nickel plating layer has a purity of up to 99.9%, is made of pure nickel, has no impurity atoms, and can completely cover the aluminum-based substrate. In some examples, the nickel plating layer covers all surfaces of the aluminum-based substrate.
[0110] Through observation under a scanning electron microscope (SEM) or a transmission electron microscope (TEM), the nickel coating prepared by the first electroplating treatment described above in the embodiment of the present disclosure has a unit cell diameter less than or equal to 100 nm, and the lattice in the nickel coating is dense, making the nickel coating uniform and dense.
[0111] In step S14, the second composite material intermediate is subjected to a second electroplating treatment, so that a second metal coating layer is formed on the surface of the first metal coating layer, thereby obtaining an aluminum-based composite material.
[0112] Exemplarily, the first metal coating is a nickel coating, the second metal coating is a nickel coating, and the second electroplating treatment uses a gold plating solution. Since the gold coating obtained by electroplating has fine grain growth, a dense and uniform gold coating is electroplated on the surface of the nickel coating, which can effectively resist oxidation and corrosion.
[0113] In some examples, the gold plating solution provided by the embodiments of the present disclosure includes the following components: 10g / L-20g / L gold trichloride, 50g / L-130g / L sodium sulfite, 30g / L-50g / L ethylenediaminetetraacetic acid, 30g / L-50g / L citric acid, 50g / L-80g / L potassium chloride, and the balance is water. The gold plating solution using the above formula has the advantages of increasing the plating rate, making the coating thickness uniform, the gold plating process stable and controllable, and the gold plating layer dense and flat.
[0114] The concentration of gold trichloride includes but is not limited to: 10g / L, 11g / L, 12g / L, 13g / L, 14g / L, 15g / L, 16g / L, 17g / L, 18g / L, 19g / L, 20g / L, etc.
[0115] The concentration of sodium sulfite includes but is not limited to: 50g / L, 55g / L, 60g / L, 65g / L, 70g / L, 75g / L, 80g / L, 85g / L, 90g / L, 95g / L, 100g / L, 105g / L, 110g / L, 115g / L, 120g / L, 125g / L, 130g / L, etc.
[0116] The concentration of EDTA includes but is not limited to: 30g / L, 33g / L, 35g / L, 37g / L, 40g / L, 42g / L, 43g / L, 44g / L, 45g / L, 46g / L, 47g / L, 48g / L, 49g / L, 50g / L, etc.
[0117] The concentration of citric acid includes but is not limited to: 30g / L, 32g / L, 35g / L, 38g / L, 39g / L, 40g / L, 42g / L, 43g / L, 44g / L, 45g / L, 46g / L, 47g / L, 48g / L, 49g / L, 50g / L, etc.
[0118] The concentration of potassium chloride includes but is not limited to: 50g / L, 52g / L, 55g / L, 57g / L, 60g / L, 63g / L, 65g / L, 68g / L, 70g / L, 72g / L, 75g / L, 76g / L, 79g / L, 80g / L, etc.
[0119] In some examples, during the gold electroplating process, the current density is 0.1ASD-5ASD, and the electroplating temperature is 30° C.-45° C. By defining the operating parameters of the gold electroplating as above, it has the advantages of increasing the plating rate, making the plating film thickness uniform, stabilizing and controllable the gold plating process, and making the gold plating layer dense and flat.
[0120] According to tests, the plating rate of the embodiment of the present disclosure during gold plating can reach 1.5 μm / min, compared with 0.15 μm / min for chemical plating, which shortens the process time of the embodiment of the present disclosure by 5 to 10 times.
[0121] Exemplarily, the current density includes but is not limited to 0.2ASD, 0.21ASD, 0.22ASD, 0.23ASD, 0.24ASD, 0.25ASD, 0.26ASD, 0.27ASD, 0.28ASD, 0.29ASD, 0.3ASD, 0.31ASD, 0.32ASD, 0.33ASD, 0.34ASD, 0.35ASD, 0.36ASD, 0.37ASD, 0.38ASD, 0.39ASD, 0.4ASD, 0.45ASD, 0.47ASD, 0.5ASD, 0.6ASD, 0.7ASD, 0.8ASD, 0.9ASD, 1ASD, 2ASD, 3ASD, 4ASD, 5ASD, etc.
[0122] Electroplating temperatures include but are not limited to: 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, etc.
[0123] In some examples, the gold plating time may be 1 minute to 5 minutes, and the thickness of the gold plating layer may be controlled by controlling at least one of the current density and the plating time. Exemplarily, the thickness of the gold plating layer may be 0.1 μm to 2 μm.
[0124] The gold plating has a purity of up to 99.9% and is made of pure gold without any impurity atoms, and can completely cover the nickel plating. In some examples, the gold plating is coated on all surfaces of the nickel plating, and post-processing can be performed according to actual needs to remove the gold plating and nickel plating on one or more surfaces, so that one or more surfaces of the aluminum-based composite material expose the aluminum-based substrate. Of course, at least one surface of the aluminum-based composite material has both the gold plating and the nickel plating.
[0125] Through SEM or TEM observation, the gold-plated layer prepared by the second electroplating treatment in the embodiment of the present disclosure has a unit cell diameter less than or equal to 100 nm, and the lattice in the gold-plated layer is dense, making the gold-plated layer uniform and dense.
[0126] In some possible implementations, the method for preparing the aluminum-based composite material provided in the embodiment of the present disclosure also includes: before the purified aluminum-based substrate is galvanized, the surface of the purified aluminum-based substrate is etched to form a rough structure on the surface of the purified aluminum-based substrate, and the rough structure is used to enhance the bonding force between the aluminum-based substrate and the nickel plating layer.
[0127] See also Figure 2 That is to say, the method for preparing the aluminum-based composite material provided by the embodiment of the present disclosure includes:
[0128] Step S21, purifying the aluminum-based substrate to obtain a purified aluminum-based substrate.
[0129] Step S22: performing surface etching treatment on the purified aluminum-based substrate so that a rough structure is formed on the surface of the purified aluminum-based substrate.
[0130] Step S23, forming a metal protective layer on the surface of the aluminum-based substrate having a rough structure to obtain a first composite material intermediate.
[0131] Step S24, performing a first electroplating treatment on the first composite material intermediate, so that the metal protective layer is corroded by the first metal plating layer, thereby forming a first metal plating layer on the surface of the aluminum-based substrate, and obtaining a second composite material intermediate.
[0132] Step S25, performing a second electroplating treatment on the second composite material intermediate, so that a second metal coating is formed on the surface of the first metal coating, thereby obtaining an aluminum-based composite material.
[0133] Through etching, a rough structure is formed on the surface of the purified aluminum-based substrate to increase its specific surface area, which is conducive to enhancing the bonding strength between the aluminum-based substrate and the first metal coating. The size of the rough structure is micro-nano scale, thereby ensuring that the surface bonding strength of the aluminum-based substrate is enhanced while not affecting its surface flatness.
[0134] In some examples, in order to make the size (e.g., depth) of the rough structure more easily controllable, the cleaned aluminum-based substrate is placed in an etching solution for surface etching, wherein the size of the formed rough structure can be correspondingly controlled by controlling the etching time.
[0135] Exemplarily, the etching solution includes components in the following proportions, so that it has the advantages of low etching rate and uniform etching: 10g / L-50g / L of tetramethylammonium hydroxide, 10g / L-50g / L of disodium ethylenediaminetetraacetate (EDTA2Na), 5g / L-20g / L of zinc oxide, 5g / L-20g / L of barbituric acid, 0.1g / L-1g / L of soluble silver salt, and water as the balance so that the pH value of the etching solution is 10-13.
[0136] The concentration of tetramethylammonium hydroxide includes but is not limited to: 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, etc.
[0137] The concentration of disodium edetate includes but is not limited to: 10g / L, 15g / L, 20g / L, 25g / L, 30g / L, 35g / L, 40g / L, 45g / L, 50g / L, etc.
[0138] The concentration of zinc oxide includes but is not limited to: 5g / L, 8g / L, 10g / L, 12g / L, 15g / L, 16g / L, 18g / L, 20g / L, etc.
[0139] The concentration of barbituric acid includes but is not limited to: 5g / L, 7g / L, 10g / L, 12g / L, 15g / L, 17g / L, 18g / L, 20g / L, etc.
[0140] The soluble silver salt can be silver nitrate, silver fluoride, silver chlorate, silver perchlorate, etc. The concentration of the soluble silver salt includes but is not limited to: 0.1g / L, 0.2g / L, 0.3g / L, 0.4g / L, 0.5g / L, 0.6g / L, 0.7g / L, 0.8g / L, 0.9g / L, 1g / L, etc.
[0141] In some examples, the purified aluminum-based substrate can be placed in an etching solution and immersed at 20°C-40°C for 1 min-5 min to perform surface etching treatment, thereby obtaining a micro-nano-sized rough structure on the surface of the aluminum-based substrate. For example, the immersion temperature includes but is not limited to 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C, 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, etc. The immersion time includes but is not limited to 1 min, 2 min, 3 min, 4 min, 5 min, etc.
[0142] In summary, the preparation method of the aluminum-based composite material provided in the embodiment of the present disclosure can effectively avoid the phenomena of loose coating and nickel nodules in chemical nickel-gold, eliminate adverse factors such as black disk and Giovanni effect, and is easy to operate, low in cost, and can effectively protect the aluminum-based substrate.
[0143] On the other hand, an embodiment of the present disclosure provides an aluminum-based composite material, which includes an aluminum-based substrate, a first metal coating, and a second metal coating arranged in sequence, wherein the unit cell diameter of the first metal coating is less than or equal to 100 nm, and the unit cell diameter of the second metal coating is less than or equal to 100 nm.
[0144] The unit cell diameter of the first metal coating involved in the embodiment of the present disclosure refers to the diagonal length of a single unit cell in the SEM image of the unit cell of the first metal coating. The unit cell diameter of the second metal coating involved in the embodiment of the present disclosure refers to the diagonal length of a single unit cell in the SEM image of the unit cell of the second metal coating.
[0145] Exemplarily, the first metal coating is a nickel coating, the second metal coating is a gold coating, and the aluminum-based composite material comprises an aluminum-based substrate, a nickel coating and a gold coating arranged in sequence, wherein the unit cell diameter of the nickel coating is less than or equal to 100 nm; the unit cell diameter of the gold coating is less than or equal to 100 nm.
[0146] The unit cell diameter of the nickel-plated layer and the unit cell diameter of the gold-plated layer can be measured by a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0147] The unit cell of nickel (Ni) crystal is a face-centered cube, i.e., a face-centered cubic close-packed structure, with one nickel atom at each of the eight vertices and the center of the six faces of the cube. The unit cell diameter of the nickel plating involved in the embodiment of the present disclosure refers to the diagonal length of a single unit cell in the SEM image of the unit cell characterizing the nickel plating.
[0148] The unit cell of a gold (Au) crystal is a face-centered cube, i.e., a face-centered cubic close-packed structure, with one gold atom at each of the eight vertices and the center of the six faces of the cube. The unit cell diameter of the gold-plated layer involved in the embodiments of the present disclosure refers to the diagonal length of a single unit cell in a SEM image of a unit cell representing the gold-plated layer.
[0149] The aluminum-based composite material provided by the embodiment of the present disclosure has a unit cell diameter of a nickel coating less than or equal to 100 nm, and a dense lattice in the nickel coating, so that the nickel coating is uniform and dense. The unit cell diameter of a gold coating is less than or equal to 100 nm, and a dense lattice in the gold coating, so that the gold coating is uniform and dense, and has an excellent covering effect on the nickel coating. The dense nickel coating and gold coating avoid mutual diffusion of nickel and gold elements, thereby avoiding the Giovanni effect and the black pad problem, which not only improves the stability of the nickel coating and the gold coating, making their corrosion resistance and oxidation resistance more stable, but also the gold coating with a flat surface and uniform texture is also conducive to welding and gold wire bonding.
[0150] In some implementations, after testing, in the aluminum-based composite material provided by the embodiments of the present disclosure, the surface roughness of the nickel plating layer is Ra≤20nm, and the surface roughness of the gold plating layer is Ra≤20nm.
[0151] Based on the above parameters, it can be seen that both the nickel plating layer and the gold plating layer maintain a high degree of flatness, which is particularly beneficial for improving their density, oxidation resistance, corrosion resistance and other properties.
[0152] In some possible implementations, the surface of the aluminum-based substrate combined with the nickel-plated layer has a rough structure, and the rough structure is used to enhance the bonding force between the aluminum-based substrate and the first metal plating layer, such as the nickel plating layer, so that the first metal plating layer is stably attached to the aluminum-based substrate. The formation method and scale of the rough structure are as described above.
[0153] In some examples, the aluminum-based composite material may be a pad structure.
[0154] On the other hand, an embodiment of the present disclosure further provides an electronic device, which includes a device body and a pad structure, wherein the pad structure is connected to the device body, and the pad structure is prepared from any one of the above-mentioned aluminum-based composite materials.
[0155] The manufacturing method mentioned above in the embodiment of the present disclosure can be used to directly process the device body with the aluminum-based material pad, and the aluminum-based material pad thereon is plated with a metal protective layer (e.g., a zinc layer), a first metal plating layer (e.g., electroplated nickel), and a second metal plating layer (e.g., electroplated gold). The pad structure can also be directly prepared using a finished aluminum-based composite material, and then the pad structure is connected to the device body.
[0156] The electronic device provided by the embodiments of the present disclosure has all the advantages of the aluminum-based composite material provided by the embodiments of the present disclosure.
[0157] In some examples, the electronic device includes but is not limited to: chips, printed circuit boards, etc., and a pad structure is arranged on the chip and the printed circuit board, and the pad structure includes a conductive column and a pad, wherein the conductive column is the above-mentioned aluminum-based substrate, and the pad is the above-mentioned first metal plating layer and the second metal plating layer arranged in a stacked manner, for example, a nickel plating layer and a gold plating layer, respectively.
[0158] Electronic devices such as chips and printed circuit boards use a pad structure based on the aluminum-based composite material described in the embodiments of the present disclosure, which not only enables efficient and reliable welding operations, but can also be further used for gold wire bonding and plastic sealing.
[0159] Some specific embodiments of the present disclosure will be described in more detail below. Although the preferred embodiments of the present disclosure are described below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. If specific techniques or conditions are not indicated in the examples, they are carried out according to the techniques or conditions described in the literature in this area or according to the product instructions. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0160] Example 1-Example 3
[0161] Embodiment 1 to Embodiment 3 respectively provide a method for preparing an aluminum-based composite material and an aluminum-based composite material obtained based on the preparation method. The preparation methods of the aluminum-based composite materials involved in Embodiment 1 to Embodiment 3 are as follows, and the difference lies in the parameters shown in Table 1:
[0162] Step 1: Place the aluminum-based substrate in a decontamination solution and soak it at 50° C. for 5 minutes, using the decontamination solution to decompose organic impurities such as grease and dirt on the aluminum-based substrate to obtain a purified aluminum-based substrate.
[0163] The impurity removal solution includes the following components: 20 g / L sodium hydroxide, 30 g / L sodium carbonate, 10 g / L sodium phosphate, 10 g / L dimethylamine borane, 50 g / L nonylphenol polyoxyethylene ether, and water as the balance so that the pH value of the impurity removal solution is 9.
[0164] Step 2: Place the purified aluminum-based substrate in an etching solution and soak it at 30° C. for 2 minutes to perform surface etching on the aluminum-based substrate.
[0165] The etching solution includes the following components: 30 g / L tetramethylammonium hydroxide, 30 g / L EDTA2Na, 10 g / L zinc oxide, 10 g / L barbituric acid, 5 g / L silver nitrate, and water as the balance so that the pH value of the etching solution is 13.
[0166] Step 3: placing the purified aluminum-based substrate in a galvanizing solution, performing a galvanizing treatment at 25° C. for 10 minutes, then placing it in a nitric acid solution with a mass concentration of 30% and pickling it at 25° C. for 2 minutes, then continuing to place it in a new galvanizing solution and performing a galvanizing treatment at 25° C. for 8-15 minutes, forming a zinc layer on the surface of the purified aluminum-based substrate to obtain a first composite material intermediate.
[0167] The thickness of the formed zinc layer is determined according to the time of the secondary galvanizing. The thickness of the zinc layer in each embodiment can be seen in Table 1. The zinc plating solution includes the following components in the following proportions: 100 g / L of sodium hydroxide, 30 g / L of potassium sodium tartrate, 5 g / L of zinc oxide, 1 g / L of ferric chloride, and water as the balance so that the pH value of the zinc plating solution is 13.
[0168] Step 4: electroplating the first composite material intermediate with nickel so that the metal protective layer is corroded by the nickel plating solution, thereby forming a nickel plating layer on the surface of the aluminum-based substrate to obtain a second composite material intermediate.
[0169] The thickness of the nickel plating layer formed is determined according to the time of the nickel electroplating treatment. The time of the nickel electroplating treatment and the thickness of the nickel plating layer in each embodiment can be seen in Table 1.
[0170] During nickel electroplating, the current density is 1.5ASD, the electroplating temperature is 55°C, and the nickel plating solution used includes the following components: 30g / L nickel sulfate, 25g / L nickel chloride, 20g / L nickel methanesulfonate, 30g / L hydrochloric acid, 8g / L dibenzenesulfonylsulfinic acid (BBI), 0.5g / L sodium styrenesulfonate, and the balance is water.
[0171] Step 5: electroplating the second composite material intermediate with gold so that a gold plating layer is formed on the surface of the nickel plating layer to obtain an aluminum-based composite material.
[0172] The thickness of the gold plating layer formed is determined according to the time of the gold electroplating treatment. The time of the gold electroplating treatment and the thickness of the gold plating layer in each embodiment can be seen in Table 1.
[0173] During the gold electroplating treatment, the current density is 0.3ASD, the electroplating temperature is 37°C, and the gold plating solution used includes the following components: 15g / L gold trichloride, 100g / L sodium sulfite, 45g / L ethylenediaminetetraacetic acid, 30g / L citric acid, 60g / L potassium chloride, and the balance is water.
[0174] Comparative Example 1-Comparative Example 2
[0175] Comparative Examples 1 and 2 respectively provide aluminum-based composite materials obtained based on chemical plating. Before chemical nickel plating and chemical gold plating, the aluminum-based substrates in Comparative Examples 1 and 2 are cleaned, etched and galvanized in sequence. The purification, etching and galvanizing processes can refer to the purification, etching and galvanizing processes described in Examples 1 to 3.
[0176] The chemical nickel plating solution used in the chemical nickel plating is a commercial product purchased from Uyemura Company and has a model of NMR-2. The chemical nickel plating temperature is 80° C. and the time is 15 min.
[0177] The chemical gold plating solution used in the chemical gold plating is a commercial product purchased from Uyemura Company and the models are TUF-1 (Comparative Example 1) and TUF-41 (Comparative Example 2). The chemical gold plating temperature of Comparative Example 1 is 74°C, and the chemical gold plating temperature of Comparative Example 2 is 50°C.
[0178] Some parameters that are different in the aluminum-based composite materials and preparation methods thereof provided in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1.
[0179] Table 1
[0180] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Aluminum base material Pure aluminum Pure aluminum Aluminum-Copper Alloy Aluminum-Silicon-Copper Alloy Pure aluminum Zinc layer thickness 10nm 20nm 10nm 10nm 5nm Nickel plating thickness 1.5μm 3μm 1.5μm 3μm 1.5μm Nickel plating time 3min 5min 3min 5min 3min Gold plating thickness 0.1μm 0.3μm 0.1μm 0.3μm 0.1μm Gilded Time 1min 2.5min 1min 2.5min 1min
[0181] Test Example 1
[0182] According to the package wire bonding strength test performed according to the standard JESD22-B116, this test example 1 performs a gold wire bonding (gold wire bonding) solder joint tensile test on the aluminum-based composite materials provided by Examples 1-3 and Comparative Examples 1-2.
[0183] The minimum tensile force value of the solder joint obtained by the tensile test of the gold wire bonding solder joint is shown in Table 2.
[0184] Table 2
[0185] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Minimum pulling force 13.7g 14.6g 13.8g 13.5g 12.1g
[0186] It can be seen from Table 2 that in the aluminum-based composite materials provided in Examples 1-3, after the coating is used as a pad and bonded with a gold wire, the bonding strength is stronger than that of the control example, which indicates that the obtained coating is flat and uniform, has high density, and is conducive to improving the gold wire bonding effect.
[0187] Test Example 2
[0188] In this test example 2, the surface morphology of the nickel plating layer in the aluminum-based composite material provided in Example 1 and the aluminum-based composite material provided in Comparative Example 2 was tested by SEM. The nickel plating layer was exposed on the surface of the aluminum-based substrate of the second composite intermediate. That is, the nickel plating layer of the second composite intermediate of the corresponding aluminum-based composite material can be tested by SEM. The test results are shown in Figure 3 and Figure 4 .
[0189] Figure 3 The magnified morphologies of the nickel-plated layer of the aluminum-based composite material provided in Example 1 at different magnifications are illustrated, wherein the magnifications of the scanning electron microscope are 1K, 5K, 20K, 50K, and 100K, respectively.
[0190] Figure 4 The magnified morphologies of the nickel-plated layer of the aluminum-based composite material provided in Comparative Example 1 at different magnifications are illustrated, wherein the magnifications of the scanning electron microscope are 1K, 5K, 20K, 50K, and 100K, respectively.
[0191] Depend on Figure 3 It can be seen that the nickel plating layer of the aluminum-based composite material provided in Example 1 has a flat and uniform surface, a dense lattice, no nodules and holes, and a small unit cell size (<100nm), which makes it highly stable and can effectively resist oxidation and corrosion.
[0192] Depend on Figure 4 It can be seen that the nickel plating layer of the aluminum-based composite material provided in Comparative Example 1 has a nodular surface, a large unit cell size (>200nm), poor flatness, and a small number of holes in some areas, which makes it poorly stable and easily accelerates corrosion.
[0193] In this test example 2, the surface morphology of the gold-plated layer in the aluminum-based composite material provided in Example 1 and the aluminum-based composite material provided in Comparative Example 2 was tested by SEM. Figure 5 and Figure 6 .
[0194] Figure 5 The magnified morphologies of the gold-plated layer of the aluminum-based composite material provided in Example 1 at different magnifications are illustrated, wherein the magnifications of the scanning electron microscope are 1K, 5K, 20K, 50K, and 100K, respectively.
[0195] Figure 6 The magnified morphologies of the gold-plated layer of the aluminum-based composite material provided in Comparative Example 1 at different magnifications are illustrated, wherein the magnifications of the scanning electron microscope are 1K, 5K, 20K, 50K, and 100K, respectively.
[0196] Depend on Figure 5It can be seen that the gold-plated layer of the aluminum-based composite material provided in Example 1 has a flat and uniform surface, a dense lattice, no nodules and holes, and a small unit cell size (<100 nm), which makes it highly stable and can effectively resist oxidation and corrosion.
[0197] Depend on Figure 6 It can be seen that the gold-plated layer of the aluminum-based composite material provided in Comparative Example 1 continues the surface morphology of the nickel-plated layer, has poor film continuity, and has loose grain boundaries, which makes it poor in stability and easily accelerates corrosion.
[0198] The above description is only for the purpose of facilitating those skilled in the art to understand the technical solution of the present disclosure and is not intended to limit the present disclosure. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.
Claims
1. A method for preparing an aluminum-based composite material, characterized in that: The preparation method of the aluminum-based composite material comprises: Purifying the aluminum-based substrate to obtain a purified aluminum-based substrate; forming a metal protective layer on the surface of the purified aluminum-based substrate to obtain a first composite material intermediate; Performing a first electroplating treatment on the first composite intermediate so that the metal protective layer is corroded to form a first metal plating layer on the surface of the aluminum-based substrate to obtain a second composite intermediate; The second composite material intermediate is subjected to a second electroplating treatment to form a second metal coating layer on the surface of the first metal coating layer, thereby obtaining the aluminum-based composite material.
2. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The metal protective layer includes a zinc layer.
3. The method for preparing the aluminum-based composite material according to claim 2, characterized in that: The step of forming a metal protective layer on the surface of the purified aluminum-based substrate to obtain a first composite material intermediate comprises: Placing the purified aluminum-based substrate in a zinc plating solution for zinc plating, forming a zinc layer on the surface of the purified aluminum-based substrate, and obtaining a first composite material intermediate; The zinc plating solution comprises the following components: 50g / L-200g / L of sodium hydroxide, 5g / L-50g / L of potassium sodium tartrate, 1g / L-10g / L of zinc oxide, 0.2g / L-2g / L of iron and ferrous compounds, and water as the balance so that the pH value of the zinc plating solution is 12-14.
4. The method for preparing the aluminum-based composite material according to claim 1, characterized in that: The thickness of the metal protection layer is 1nm-100nm.
5. The method for preparing the aluminum-based composite material according to any one of claims 1 to 4, characterized in that: The first metal coating comprises a nickel coating or a nickel-phosphorus alloy coating; The second metal plating layer includes a gold plating layer.
6. The method for preparing the aluminum-based composite material according to claim 5, characterized in that: The first metal coating is a nickel coating, and the first electroplating treatment uses a nickel plating solution, which includes components in the following proportions: 1g / L-50g / L nickel sulfate, 1g / L-50g / L nickel chloride, 1g / L-50g / L nickel methanesulfonate, 1g / L-50g / L hydrochloric acid, 1g / L-10g / L main brightener, 0.1g / L-1g / L auxiliary brightener, and the balance is water.
7. The method for preparing the aluminum-based composite material according to claim 6, characterized in that: When performing the first electroplating treatment, the current density is 0.1ASD-5ASD, and the electroplating temperature is 45°C-65°C.
8. The method for preparing the aluminum-based composite material according to claim 5, characterized in that: The second metal plating layer is a gold plating layer, and the second electroplating treatment adopts a gold plating solution, which includes components in the following proportions: 10g / L-20g / L of gold trichloride, 50g / L-130g / L of sodium sulfite, 30g / L-50g / L of ethylenediaminetetraacetic acid, 30g / L-50g / L of citric acid, 50g / L-80g / L of potassium chloride, and the balance is water.
9. The method for preparing the aluminum-based composite material according to claim 8, characterized in that: When the second electroplating treatment is performed, the current density is 0.1ASD-5ASD, and the electroplating temperature is 30°C-45°C.
10. The method for preparing the aluminum-based composite material according to any one of claims 1 to 9, characterized in that: The method for preparing the aluminum-based composite material further comprises: before the purified aluminum-based substrate is subjected to galvanizing, the purified aluminum-based substrate is subjected to surface etching treatment, so that a rough structure is formed on the surface of the purified aluminum-based substrate; The rough structure is used to enhance the bonding force between the aluminum-based substrate and the first metal coating layer.
11. The method for preparing the aluminum-based composite material according to claim 10, characterized in that: The surface etching treatment is performed by placing the cleaned aluminum-based substrate in an etching solution; The etching solution comprises the following components: 10g / L-50g / L tetramethylammonium hydroxide, 10g / L-50g / L disodium ethylenediaminetetraacetate, 5g / L-20g / L zinc oxide, 5g / L-20g / L barbituric acid, 0.1g / L-1g / L soluble silver salt, and water as the balance so that the pH value of the etching solution is 10-13.
12. An aluminum-based composite material, characterized in that: The aluminum-based composite material comprises an aluminum-based substrate, a first metal coating and a second metal coating which are sequentially stacked; The unit cell diameter of the first metal coating is less than or equal to 100 nm; The unit cell diameter of the second metal coating layer is less than or equal to 100 nm.
13. The aluminum-based composite material according to claim 12, characterized in that: The aluminum-based substrate has a rough structure on its surface combined with the first metal coating layer, and the rough structure is used to enhance the bonding force between the aluminum-based substrate and the first metal coating layer.
14. An electronic device, characterized in that: The electronic device comprises a device body and a pad structure connected to the device body, and the pad structure is prepared using the aluminum-based composite material according to any one of claims 12-13.
15. The electronic device according to claim 14, characterized in that The electronic device includes: a chip and a printed circuit board.
Citation Information
Cited By
Aluminum-based composite material and preparation method therefor, and electronic device
EP4745277A1
Aluminum-based composite material and preparation method therefor, and electronic device
WO2025035887A1